Fazendo e desfazendo gênero: xs drag queens de Belo Horizonte - Henrique Luiz Caproni Neto (2016)
I sought in this dissertation to understand the doing and undoing of the gender of drag queens from Belo Horizonte, using especially the works of Judith Butler (2003, 1993, 1997, 2004). The theory was structured discussing: the gender in a non-essentialist view, considering it as a doing and not a property of the subject, the criticis of the gender binary and questioning the transgender issue without intending to exhaust it given its complexity; doing and undoing the gender supporting me especially in Judith Butler, organizational and social sciences authors; (hetero) norm and the (dis) identification appropriating Butler's reflections on the subject related directly to social norms, given that the identifications are never complete, allowing differentiations and subversions; the performativity, parody and gender performance, differentiating them and recognizing the performativity imbricated with the reiteration of the discursive norms; a brief introduction to the world of drags especially focusing on Brazilian studies. Thus, I realized a qualitative research, with a poststructuralist epistemology through biographical narratives of ten drag queens, with inspiration in critical discourse analysis of Fairclough (2003, 2008). The analysis was designed from the work and concepts of Judith Butler and has the following categories: Performances that contains sub-categories: on performances, productions and caches, performances with the "straight" and "LGBTIQ" public, performances and feelings, and humor; The relationship among drags: family, "friends", "colleagues" and power games; Seeking recognition for x drag queen; Humor; (Dis) Identifications; Doing and undoing gender. Finally, considerations lead the complexity and ambivalence of this theme in the identifications, the doings, undoings and the contingentiality of the gender. Also thinking about the possibility of a direct relationship with critical organizational studies, having seen that the heteronormative matrix inhabits the administration, but does not prevent us to create rivals matrices